PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT SUKSES MAKMUR LANCAR CABANG PAGEDANGAN - Ahyari, Febri; Sina, Ibnu (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. The purpose of this study was to determine whether Competence and Organizational Culture affect Employee Performance at PT Sukses Makmur Lancar either partially or simultaneously. The research method used was a quantitative method with an associative approach. The sample used in this study was a saturated sample, namely using a population of 56 people as a sample. Data analysis used Validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis test. The results showed that there was a positive influence between the variables of Competence and Organizational Culture on Employee Performance simultaneously, where the multiple linear regression equation Y = 31.139 + 0.312 X1 + (-0.085) X2, the correlation coefficient value of , -0.393 means it has a very low level of relationship. The determination value or contribution of its influence is 15.4% and the remaining 84.6% is influenced by other variables. The hypothesis test obtained the value of Ftable> Fcount (4.827> 3.17). Thus, Ha3 is accepted, meaning that there is a significant simultaneous influence between Competence and Organizational Culture on Employee Performance at PT Sukses Makmur Lancar, Pagedangan branch. Keywords: whether Competence and Organizational Culture affect Employee Performance